Mycobacterium avium: an Emerging Pathogen for Dog Breeds with Hereditary Immunodeficiencies - Ghielmetti, Giovanni (Curr Clin Microbiol Rep, 2020)
PURPOSE OF REVIEW: Among the nontuberculous mycobacteria (NTM), Mycobacterium avium complex (MAC) is the leading cause of pulmonary disease in humans. Innate and acquired immunodeficiencies have been associated with an increased host susceptibility to NTM infections. The underlying mechanisms predisposing humans and dogs to MAC infections is being elucidated. RECENT FINDINGS: Although MAC infection is infrequently diagnosed in dogs, a strong breed predisposition particularly for Miniature Schnauzer and Basset Hound dogs is evident. A recessively inherited defect of the adaptor protein CARD9 has recently been documented to be responsible for the increased susceptibility to MAC in the Miniature Schnauzer breed. SUMMARY: Given the zoonotic potential of a MAC infected dog particularly to immunocompromised human patients, diseased dogs pose a public health risk. While not a reportable disease, treatment of systemic mycobacteriosis is generally not effective and discouraged in dogs. The collaborative efforts by microbiologists, veterinary clinicians, dog breeders, primary care physicians, and infectious disease specialists applying the One Health approach is therefore crucial for the best management and prevention of MAC infection.